2018
DOI: 10.1017/s0967199418000047
|View full text |Cite
|
Sign up to set email alerts
|

l-Ergothioneine improves the developmental potential of in vitro sheep embryos without influencing OCTN1-mediated cross-membrane transcript expression

Abstract: SummaryThe objective of the study was to investigate the effect of l-ergothioneine (l-erg) (5 mM or 10 mM) supplementation in maturation medium on the developmental potential and OCTN1-dependant l-erg-mediated (10 mM) change in mRNA abundance of apoptotic (Bcl2, Bax, Casp3 and PCNA) and antioxidant (GPx, SOD1, SOD2 and CAT) genes in sheep oocytes and developmental stages of embryos produced in vitro. Oocytes matured with l-erg (10 mM) reduced their embryo toxicity by decreasing intracellular ROS and increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Interestingly, we observed that both SOD1 and SOD2 were upregulated in the ESH-treated hepatocytes against AZA. The SOD upregulating effect of ESH has been document already (Mishra et al 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, we observed that both SOD1 and SOD2 were upregulated in the ESH-treated hepatocytes against AZA. The SOD upregulating effect of ESH has been document already (Mishra et al 2018).…”
Section: Discussionmentioning
confidence: 98%
“…The antioxidant enzyme activity is strongly regulated by estrogen in females, and total SOD activity is more in females than in males 45 . Antioxidant-mediated upregulated expression of GPX and SOD2 in ovine embryos is evident 46 . Hence, overexpression of these antioxidant genes at low oxidative status in female embryos enhanced the antioxidant mediated defense against oxidative stress, resulting in better female embryos development.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to protect oocytes from oxidative stress during IVM. EGT supplementation during IVM, IVF, and in vitro culture had a beneficial effect on the IVM of oocytes and embryo developmental competence [ 41 ]. These beneficial effects of EGT could be used in the potential applications of EGT in IVF.…”
Section: Discussionmentioning
confidence: 99%